2012
DOI: 10.1364/oe.20.028301
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and polarization properties of a radially polarized beam with variable spatial coherence

Abstract: In a recent publication [Appl. Phys. Lett, 100, 051108 (2012)], a radially polarized (RP) beam with variable spatial coherence (i.e., partially coherent RP beam) was generated experimentally. In this paper, we derive the realizability conditions for a partially coherent RP beam, and we carry out theoretical and experimental study of the coherence and polarization properties of a partially coherent RP beam. It is found that after passing through a thin lens, both the degree of coherence and the degree of polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 58 publications
5
37
0
Order By: Relevance
“…It was found that the beam profile and the polarization feature of the SCRP beam in the far field become a doughnut shape and radial polarization, respectively, while such beam in the source plane can be considered as an un-polarized beam with intensity distribution being Gaussian profile. These properties are much different from a radially polarized beam with conventional Gaussian Schell-model correlation, i.e., partially coherent radially polarized (PCRP) beam [16,17], whose polarization distribution is radially polarized in the source and de-polarized on propagation due to its limited spatial coherence length.…”
Section: Introductionmentioning
confidence: 90%
“…It was found that the beam profile and the polarization feature of the SCRP beam in the far field become a doughnut shape and radial polarization, respectively, while such beam in the source plane can be considered as an un-polarized beam with intensity distribution being Gaussian profile. These properties are much different from a radially polarized beam with conventional Gaussian Schell-model correlation, i.e., partially coherent radially polarized (PCRP) beam [16,17], whose polarization distribution is radially polarized in the source and de-polarized on propagation due to its limited spatial coherence length.…”
Section: Introductionmentioning
confidence: 90%
“…As the input beam, we consider a radially polarized partially coherent beam, with Gaussian degree of coherence and donut-like intensity profile, described by the following BCP matrix [14]:…”
Section: Examplementioning
confidence: 99%
“…Since 2000, RP beam has been investigated in detail and found many applications, such as microscopy, lithography, electron acceleration, proton acceleration, material processing, optical data storage, high-resolution metrology, super-resolution imaging, plasmonic focusing and laser machining, free-space optical communications [1][2][3][4][5][6][7][8][9][10]. In the past several years, RP beam with controllable spatial coherence (i.e., PCRP beam) was introduced in theory and generated in experiment [11][12][13][14][15]. The propagation properties of a PCRP beam are quite different from those of a RP beam.…”
Section: Introductionmentioning
confidence: 99%
“…The PCRP beam exhibits the properties of depolarization on propagation in free space, i.e., the degree of polarization decreases on propagation, while its state of polarization remains radial polarization on propagation. Through varying the spatial coherence width, one can shape the beam profile of the focused beam spot of a PCRP beam [11,12], which is useful for particle trapping. Furthermore, it was found in [13] that a PCRP beam has an advantage over a linearly polarized partially coherent beam for reducing turbulence-induced scintillation, which is useful in free-space optical communications.…”
Section: Introductionmentioning
confidence: 99%